General aspects of morphological changes of the small intestine of animals suspected to babesiosis - I. I. Torianyk (Морфологія, 2020)
Background. Structural and functional changes that occur in the target organs of babesia should be used as a basis for additional criteria for the diagnosis of this infection. Objective. is to accordingly errors in diagnosis babesiosis to significant negative results. Methods. The objects of this investigations are control intact group animals(n=18) and such paterns, which were with the babesious infection (n=68). For all of clinical groups were used histological methods. Microscopic examination was carried out in a traditional way. Bits of the material were removed, washed, fixed in 12 % formaldehyde (pH= 7,0-7,2), subjected to postfixation and dehydrated. Sections were contrasted by hematoxsilin and eosin. Results. The organ is slightly swollen. Mechanical pressure provoked the appearance of a small amount of turbid fluid from under the slice. This phenomenon was regarded as the fact of increased hydration of tissue structures. Mucous membrane dull, faded, emaciated, slightly atrophic, with a characteristic yellowish tinge. Histologically: epithelium single-row prismatic with damage to the integrity and the facts of desquamation. Cells with signs of destruction of the apical surface, loss of limbic stretch marks. The structure of follicles is disorganized, areas are destroyed, blurred. Germinative centers without areas of enlightenment. The walls of microvessels are elegant, sometimes with signs of stratification, destruction, the appearance of through defects. The obvious consequence of these disorders was the development of paravasal edema and perivascular hemorrhage. Conclusion. Histological changes in the small intestine of animals susceptible to babesiosis showed no specific changes. It is obvious that babesiosis invasion has an indirect (due to intoxication products) effect on the structural components of the organ.